Análisis económico de la violencia doméstica en Colombia, 2012-2015. (2017)
This document is based on a non-cooperative model, in which if a woman works and the household presents other income, physical aggressions against women are reduced. Variables are used that influence violence by the head of the household and cause damage to the cooperative bond between the father and the woman and the family. The results show that if women have more education, are married, have more time with their partner, are older and their social stratum is higher, physical violence to women is reduced. In cases of women victims of physical aggression by the head of the household, the majority are women who are married and work.